Internationalization strategy for MyHelpster.com with a focus on international market selection - Pereira, Daniel da Eira (2016)
International Market Selection is an important step towards a successful internationalization strategy. This is no different for startup companies like MyHelpster. This work project was intended to help MyHelpster with their internationalization process by completing the IMS portion of it. The IMS process presented in this paper lead to the conclusion that MyHelpster’s next market for expansion should be the USA. In order to find as much success as possible the author suggests being patient and only expanding when the company has the necessary capital, experience and credibility. Both primary and secondary data were used to compile the qualitative and quantitative analyses.